Positive electrode active material, method for preparing the same, and positive electrode and electrochemical device using the same
Patent Information
- Application Number
- CN202511107963.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-03-21
- Filing Date
- 2025-08-08
- Publication Date
- 2026-09-22
AI Technical Summary
然而,由于LiCoO2在锂离子脱嵌过程中其晶体结构会变得不稳定,导致热特性极差,且价格昂贵,因此在电动汽车等动力源领域大规模应用存在一定的局限性
[0034]根据本发明的一个方面,通过实现一次粒子和二次粒子的均匀生长及优异的粒子形状均一性,可改善因氧化态氧的不稳定性而引起的充放电过程中的不可逆性。
Smart Images

Figure CN122800602A_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to a positive electrode active material, and more specifically, to a positive electrode active material, its preparation method, a positive electrode, and an electrochemical device. [Background Technology]
[0002] With the development of mobile device technology and the increasing demands, the demand for secondary batteries as an energy source has risen sharply. Among these secondary batteries, lithium secondary batteries, which have high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used.
[0003] The positive electrode active material for lithium-ion secondary batteries mainly uses lithium transition metal composite oxides. Among them, lithium cobalt composite metal oxides (such as LiCoO2), known for their high operating voltage and excellent capacity characteristics, are widely used. However, because the crystal structure of LiCoO2 becomes unstable during lithium-ion insertion and extraction, resulting in extremely poor thermal properties and high cost, its large-scale application in power sources such as electric vehicles is somewhat limited.
[0004] To address these issues, overlithiated layered oxide (OLO) was proposed. However, the oxidation / reduction reaction of oxygen generates oxidized oxygen species (On-) in the cathode structure, leading to structural instability and subsequent continuous structural degradation during charge and discharge. Furthermore, the irreversibility caused by oxygen release and other factors also severely impacts battery performance.
[0005] [Previous Technical Documents]
[0006] [Patent Document] Korean Patent Publication No. 10-2023-0051828A (published on April 19, 2023). [Summary of the Invention]
[0007] According to one aspect of the present invention, a positive electrode active material capable of improving the performance of electrochemical devices is provided.
[0008] According to another aspect of the present invention, a positive electrode active material is provided that can improve the irreversibility of the charge-discharge process caused by the instability of oxidized oxygen.
[0009] According to another aspect of the present invention, a positive electrode active material is provided in which primary and secondary particles are grown uniformly, the particle shape is highly uniform, and the structural stability is improved.
[0010] According to another aspect of the present invention, a positive electrode active material is provided that can improve the lithium ion migration speed and thus improve the charge and discharge rate of electrochemical devices.
[0011] According to another aspect of the present invention, a positive electrode comprising the said positive electrode active material is provided.
[0012] According to another aspect of the present invention, an electrochemical device with high charging capacity, high discharging capacity and high coulombic efficiency is provided.
[0013] The objectives of this invention are not limited to those listed above. Other objectives and advantages not mentioned herein will be understood through the following description and will become more apparent through embodiments of the invention. Furthermore, it is obvious that the objectives and advantages of this invention can be achieved through the means and combinations thereof described in the specification.
[0014] According to one aspect of the present invention, a positive electrode active material comprising an overlithiated layered oxide (OLO) and satisfying an R value not exceeding 27 calculated by the following formula (1) is provided.
[0015]
Equation (1)
[0016] According to SAXS (small-angle X-ray scattering) analysis: In the above equation (1), P A This indicates the volume (cm³) of macropores included in the positive electrode active material. 3 / g), P B This indicates the volume (cm³) of the micropores included in the positive electrode active material. 3 / g). Among them, the macropores have a radius of to The maximum volume fraction is observed within the interval. The micropores have a radius of to The maximum volume fraction is observed within the interval.
[0017] Preferably, the positive electrode active material may comprise a compound represented by the following general formula (1).
[0018]
General Formula (1)
[0019] In the above general formula (1), 0 < x < 1, a + b + c = 1, and 0 < a < 1, 0 ≤ b < 1, 0 ≤ c < 1, M1 and M2 are different transition metals selected from Ni or Co.
[0020] Preferably, the positive electrode active material may comprise a compound represented by the following general formula (2).
[0021]
General Formula (2)
[0022] In the above general formula (2): M3 and M4 are independently selected from the group consisting of Zr, Al, Re, V, Cr, Fe, Ga, Si, B, Ru, Ti, Nb, Mo, Mg, W, Na and Pt; 0.500 < y < 0.800, 0.450 < p < 0.650, 0 ≤ q ≤ 0.025, 0 ≤ r ≤ 0.100, 0.900 ≤ s ≤ 1.000.
[0023] Preferably, according to XRD (X-ray diffraction) analysis: the X-ray intensity (I) at the (104) diffraction peak (104) Under the condition that the X-ray intensity of the (003) diffraction peak is (I) (003) The ratio of (I) (003) / I (104) A positive electrode active material with a value of not less than 1.31 can be provided.
[0024] Preferably, according to SAXS (small-angle X-ray scattering) analysis, the pore volume of the macropore can be 0.35 cm³. 3 / g or more and not exceeding 0.45cm 3 / g.
[0025] Preferably, according to SAXS (small-angle X-ray scattering) analysis, the pore volume of the above-mentioned micropores can be 0.017 cm³. 3 / g or more and not exceeding 0.025cm 3 / g.
[0026] Preferably, according to SAXS (small-angle X-ray scattering) analysis, the total pore volume contained in the positive electrode active material does not exceed 0.475 cm³. 3 / g.
[0027] According to another aspect of the present invention, a method for preparing a positive electrode active material is provided, the method comprising: (S1) preparing a mixture comprising a lithium-permeable layered oxide precursor and a lithium precursor; and (S2) heat-treating the mixture to prepare the positive electrode active material, wherein, in the preparation reaction of the positive electrode active material, the molar content of the lithium precursor is lower than the molar content required by stoichiometry.
[0028] Preferably, the molar content of the lithium precursor may be 0.5 to 3 moles lower than the stoichiometric molar content.
[0029] Preferably, step (S2) may include a heat treatment step of heating the mixture in air at a temperature of 800°C to 1100°C for 0.5 hours to 15 hours.
[0030] According to another aspect of the present invention, a positive electrode active material prepared by the above-described positive electrode active material preparation method is provided.
[0031] According to another aspect of the present invention, a positive electrode comprising the positive electrode active material described in several embodiments is provided.
[0032] According to another aspect of the present invention, an electrochemical device is provided, the device comprising a positive electrode, a negative electrode, a membrane disposed between the positive electrode and the negative electrode as described in several embodiments, and an electrolyte.
[0033] The solutions to the above problems are not exhaustive lists of all features of the present invention, but can be combined with several embodiments described in this specification. The various features of the present invention, and the advantages and effects therefrom, can be understood in more detail through the following specific description.
[0034] According to one aspect of the present invention, by achieving uniform growth of primary and secondary particles and excellent particle shape uniformity, the irreversibility of the charge-discharge process caused by the instability of oxidized oxygen can be improved.
[0035] According to another aspect of the present invention, a positive electrode active material that improves the lithium-ion migration speed and thus the charge-discharge speed of electrochemical devices can be realized.
[0036] According to another aspect of the present invention, an electrochemical device with high charging capacity, high discharging capacity and high coulombic efficiency can be realized.
[0037] In addition to the effects described above, the specific effects of the present invention will be further explained below in the section on the specific implementation of the present invention. Furthermore, the effects of the present invention are not limited to those described above, and can also be easily achieved by the means and combinations thereof described in the specification. [Attached Image Description]
[0038] Figure 1a It is a 1 / 4 nickel and 3 / 4 manganese carbonate (Ni) prepared according to the preparation example. 0.25 Mn 0.75 SEM-EDS (Scanning Electron Microscopy-Energy Dispersive Spectroscopy) analysis results of CO3.
[0039] Figure 1b It is the preparation example of one-quarter nickel and three-quarters manganese carbonate (Ni 0.25 Mn 0.75 XRD (X-ray diffraction) analysis results of CO3.
[0040] Figure 2 The results are XRD analysis of the positive electrode active materials obtained in Comparative Examples 1, 2 and the Examples.
[0041] Figure 3a The results are XRD analysis of the positive electrode active material obtained in Comparative Example 1.
[0042] Figure 3b The results are XRD analysis of the positive electrode active material obtained in Comparative Example 2.
[0043] Figure 3c The results are XRD analysis of the positive electrode active material obtained in the examples.
[0044] Figure 4a This is a SEM (scanning electron microscope) image of the positive electrode active material obtained in Comparative Example 1. Figure 4b yes Figure 4a Enlarged SEM image.
[0045] Figure 5a This is a SEM image of the positive electrode active material obtained in Comparative Example 2. Figure 5b yes Figure 5a Enlarged SEM image.
[0046] Figure 6a This is a SEM image of the positive electrode active material obtained in the example. Figure 6b yes Figure 6a Enlarged SEM image.
[0047] Figure 7a These are TEM (transmission electron microscopy) images of the cross-section of the positive electrode active material obtained in Comparative Examples 1, 2 and Examples.
[0048] Figure 7b These are TEM images of the atomic arrangement analysis of the positive electrode active materials obtained in Comparative Examples 1, 2 and the Examples.
[0049] Figure 8 The results are the electron energy loss spectrum (EELS) analysis results of the positive electrode active materials obtained in Comparative Example 2 and the Examples.
[0050] Figure 9a The results are SAXS (small-angle X-ray scattering) analysis results of the positive electrode active materials obtained in Comparative Examples 1, 2 and Examples.
[0051] Figure 9b The results are SAXS analysis of the volume distribution of micropore and macropore radii in the positive electrode active materials obtained in Comparative Examples 1, 2 and the Examples.
[0052] Figure 10a This is a charge / discharge curve of the electrochemical device obtained in Comparative Example 1. Figure 10b This is a charge / discharge curve of the electrochemical device obtained in Comparative Example 2. Figure 10c This is a charge / discharge curve of the electrochemical device obtained in the example.
[0053] Figure 11 This is a graph showing the capacity changes of the electrochemical devices obtained in Comparative Examples 1, 2 and the Examples at different cycle numbers.
[0054] Figure 12 The results are X-ray absorption spectra (XAS) of the transition metal oxidation state changes of the positive electrode active material in the electrochemical devices obtained in Examples 1, 2 and the embodiments.
[0055] Figure 13a The results are X-ray absorption spectra of the oxidation state changes of Ni and Mn in the electrochemical device obtained in Comparative Example 1 during the charging / discharging process.
[0056] Figure 13b The results are X-ray absorption spectra of the oxidation state changes of Ni and Mn in the electrochemical device obtained in Comparative Example 2 during the charging / discharging process.
[0057] Figure 13c The X-ray absorption spectra of the oxidation state changes of Ni and Mn during the charging / discharging process in the electrochemical device obtained in the examples are shown.
Detailed Implementation Methods
[0058] In this specification, unless the context clearly indicates otherwise, singular expressions also include plural expressions.
[0059] In this specification, terms such as "first," "second," "(S1)," and "(S2)" can be used to describe different components, and their order and importance are not fixed, nor are they used to limit related components. These terms can be used to distinguish different components. For example, without departing from the scope of protection of this invention, a first component can be referred to as a second component, and vice versa.
[0060] In this specification, when "to" is used to indicate a numerical range, the range includes the upper and lower limits stated before and after. For example, "a to b" should be understood as "a above and b below" (i.e., a ≤ x ≤ b).
[0061] When multiple upper and lower limit values are listed in this specification, the range of values should be understood as a range that can be formed by combining any one of the multiple lower limit values with any one of the multiple upper limit values. For example, when it is recorded as "a or above" or "b or above" and "c or below" or "d or below", it should be understood as a or above c, a or above d, b or above c, b or above d, etc.
[0062] The SAXS (small-angle X-ray scattering) analysis method described in this specification is an analytical tool that assesses information such as the size, volume, shape, and distribution of pores by analyzing the scattering patterns produced when X-rays interact with the positive electrode active material.
[0063] According to one aspect of the present invention, a positive electrode active material comprising an overlithiated layered oxide (OLO) is provided, wherein the R value calculated by the following formula (Equation 1) does not exceed 27.
[0064]
Formula 1
[0065] Based on SAXS (small-angle X-ray scattering) analysis: In Equation 1 above, P A This indicates the volume (cm³) of macropores contained in the positive electrode active material. 3 / g), P B This indicates the volume (cm³) of the micropores contained in the positive electrode active material. 3 / g), the macropore has a radius of / g), The interval has the maximum volume fraction (unit: The micropores have a radius of The interval has the maximum volume fraction.
[0066] The R value in the above formula (Equation 1) is a parameter derived from the change in the content of the lithium source (lithium precursor). Experimental results show that as the lithium source content is lower than the stoichiometric ratio, the volume of macropores in the positive electrode active material decreases while the volume of micropores increases, thus leading to the parameter R. When the R value in Formula (Equation 1) exceeds the above numerical range, the radius and volume of macropores will increase, which may lead to a decrease in the performance of electrochemical devices such as charging capacity, discharging capacity, and coulombic efficiency. According to one aspect of the present invention, if the R value in Formula (Equation 1) meets the above numerical range, uniform growth of primary and secondary particles can be achieved, resulting in excellent uniformity of particle shape, thereby improving the irreversibility of the charging and discharging process caused by the instability of oxidized oxygen. According to another aspect of the present invention, by controlling the R value in Formula (Equation 1) within the above numerical range, a positive electrode active material that improves the migration speed of lithium ions and thus improves the charging and discharging rate of electrochemical devices can be achieved.
[0067] The structure of the present invention will be described in more detail below.
[0068] 1. Positive electrode active material
[0069] The positive electrode active material according to the present invention includes overlithiated layered oxide (OLO).
[0070] In this specification, perlithium layered oxides are defined as compounds in which the molar ratio of lithium to all transition metals (Li / metal molar ratio) is greater than 1. For example, the perlithium layered oxide may include one or more phases.
[0071] According to the positive electrode active material of the present invention, the R value calculated in the following formula 1 satisfies the condition of not exceeding 27.
[0072]
Formula 1
[0073] According to SAXS (small-angle X-ray scattering): In Equation 1 above, P A The volume (cm³) of macropores included in the positive electrode active material. 3 / g), P B The volume (cm³) of the micropores included in the positive electrode active material. 3 / g). Among them, the macropores have a radius of It has the largest volume fraction within the range Micropores with a radius of It has the largest volume fraction within the range. The term "radius" here refers to the radius of each orifice.
[0074] SAXS (small-angle X-ray scattering) is an analytical method for studying the structural properties of nanomaterials by analyzing the intensity of X-ray scattering within small-angle regions. For example, when performing SAXS analysis on positive electrode active materials, the scattering intensity varies due to changes in the microstructure caused by the internal porosity of the particles. Analysis can output an image showing the relationship between pore size (x-axis) and pore volume fraction (y-axis), thus allowing analysis of the porous material's structure.
[0075] In this invention, by using a pore size (x-axis)-pore volume fraction (y-axis) image, macropores and micropores in general lithium-ion layered oxide cathode active materials can be distinguished and finely controlled, thereby preparing cathode active materials with excellent electrochemical performance.
[0076] In some embodiments of the present invention, the R value may be not more than 27, 26, 25, 24, 23, 22 or 21; specifically, it may be 19 or more and not more than any one of the above multiple upper limits, or 20 or more and not more than any one of the above multiple upper limits. In certain embodiments of the present invention, by regulating the R value within the above range, primary particles and secondary particles can grow uniformly, and a cathode active material with uniform particle shape can be obtained, thereby improving the irreversibility during charge and discharge caused by unstable oxidized oxygen. In addition, by controlling the R value of Formula 1 within the above range, the migration rate of lithium ions can also be increased, and a cathode active material with high charge and discharge rate can be obtained.
[0077] In other embodiments of the present invention, the cathode active material may comprise a compound represented by the following general formula 2.
[0078] [General Formula 1] xLi2MnO3·(1-x)Li[Mn a M1 b M2 c O2
[0079] In the above general formula 1, 0<x<1, a+b+c=1, and 0<a<1, 0≤b<1, 0≤c<1. M1 and M2 are different transition metals, each being Ni or Co. In the compound represented by general formula 1, x can determine the mixing ratio of the two phases. The compound represented by general formula 1 is an undoped lithium-excess layered oxide, the capacity of an electrochemical device can be increased by xLi2MnO3 therein (representing a lithium-excess state), and meanwhile the structural stability and thermal stability of the cathode active material can be improved by (1-x)Li[Mn a M1 b M2 c O2, so that both effects can be achieved simultaneously.
[0080] In other embodiments of the present invention, the cathode active material may comprise a compound represented by the following general formula 2.
[0081] [General Formula 2] y[LiMn p Ni (1-p-q-r) Co q M3 r O2]·(1-y)[Li2Mn s M4 (1-s) O3]
[0082] In the general formula 2 above, M3 and M4 are each independently one selected from the group consisting of Zr, Al, Re, V, Cr, Fe, Ga, Si, B, Ru, Ti, Nb, Mo, Mg, W, Na and Pt; 0.500<y<0.800, 0.450<p<0.650, 0≤q≤0.025, 0≤r≤0.100, 0.900≤s≤1.000. Specifically, y in general formula 2 represents the mixing ratio of two phases. The compound represented by general formula 2 is different from the compound represented by general formula 1, and may be a lithium-excess layered oxide doped with M3 and M4. Specifically, since the compound represented by general formula 2 is doped with M3 and M4, the stability of the lithium-excess structure can be enhanced, and the long-term cycling performance can be improved.
[0083] In some embodiments of the present invention, according to XRD (X-ray diffraction) analysis: the diffracted X-ray intensity of the (104) peak (I (104) ) and the diffracted X-ray intensity of the (003) peak (I (003) ) the ratio (I (003) / I (104) ) may be 1.31 or more. Specifically, the diffracted X-ray intensity of the (003) peak (I (003) ) and the diffracted X-ray intensity of the (104) peak (I (104) ) the ratio (I (003) / I (104) ) may be 1.31 or more, 1.32 or more, 1.33 or more, 1.34 or more, or 1.35 or more.
[0084] In some non-limiting examples, the diffracted X-ray intensity of the (104) peak (I (104) ) and the diffracted X-ray intensity of the (003) peak (I (003) ) the ratio (I (003) / I (104) ) is a parameter that varies according to the content of the lithium source (lithium precursor), and may be a factor affecting cation mixing caused by Li + / Ni 2+ site exchange.
[0085] In some embodiments of the present invention, by adjusting the diffracted X-ray intensity ratio of (003) / (104) (I (003) / I (104) ) to the above numerical range, cation mixing caused by cations (e.g., Li + / Ni 2+The site exchange causes cation mixing, which effectively prevents the lithium-ion migration channels from being blocked.
[0086] In some embodiments of the present invention, according to SAXS (Small-Angle X-ray Scattering) analysis, the volume of the macroscopic pores (Pore volume) can be 0.35 cm³. 3 / g or more up to 0.45cm 3 / g or less. Specifically, the volume of this macroscopic pore can be: 0.35cm³. 3 / g or more, 0.36cm 3 / g or more, 0.37cm 3 / g or more, 0.38cm 3 / g or more, 0.39cm 3 / g or more, 0.40cm 3 / g or more or 0.41cm 3 / g or more; and can be: 0.42cm 3 / g or less, 0.43cm 3 / g or less, 0.44cm 3 / g or less or 0.45cm 3 / g or less. In some embodiments of the present invention, by controlling the macroscopic pore volume within the above-mentioned numerical range, primary and secondary particles can grow uniformly, and a positive electrode active material with excellent particle morphology uniformity can be achieved, thereby improving the irreversibility of the charge and discharge process caused by the instability of oxidized oxygen.
[0087] In some embodiments of the present invention, according to SAXS (small angle X-ray scattering) analysis, the micropore volume can be 0.017 cm³. 3 / g or more up to 0.025cm 3 Below / g. Specifically, the micropore volume can be: 0.017cm³. 3 / g or more, 0.018cm 3 / g or more, 0.019cm 3 / g or more or 0.020cm 3 / g or more; and can be: 0.021cm 3 / g or less, 0.022cm 3 / g or less, 0.023cm 3 / g or less, 0.024cm 3 / g or less or 0.025cm 3 / g or less. In some embodiments of the present invention, by controlling the micropore volume within the above-mentioned numerical range, primary and secondary particles can grow uniformly, and a positive electrode active material with excellent particle morphology uniformity can be achieved, thereby improving the irreversibility of the charge and discharge process caused by the instability of oxidized oxygen.
[0088] In some embodiments of the present invention, according to SAXS (small-angle X-ray scattering) analysis, the total pore volume contained in the positive electrode active material can be 0.475 cm³. 3 / g or less. Specifically, the total pore volume contained in this positive electrode active material can be: 0.470 cm³. 3 / g or less, 0.46cm 3 / g or less or 0.45cm 3 / g or less; more specifically, it can be 0.40cm 3 / g or more and not exceeding any one of the above-mentioned upper limits. In some embodiments of the present invention, by controlling the total pore volume contained in the positive electrode active material within the above-mentioned numerical range, primary and secondary particles can grow uniformly, and a positive electrode active material with excellent particle morphology uniformity can be achieved, thereby improving the irreversibility of the charge and discharge process caused by the instability of oxidized oxygen.
[0089] In this specification, the average particle size can be defined as the particle size (D50) at which the cumulative percentage on a volume-based particle size distribution curve reaches 50% when measured by a laser diffraction particle size distribution measuring device. For example, the particles to be tested can be dispersed in a dispersion medium and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500). As the particles pass through the laser beam, the particle size distribution is calculated by measuring the difference in diffraction patterns caused by their particle size.
[0090] In some embodiments of the present invention, the positive electrode active material may be secondary particles formed by the aggregation of primary particles. In some non-limiting examples, the average particle size of the primary particles may be 50 to 100 nm, and the average particle size of the secondary particles may be 7 to 9 μm.
[0091] In some embodiments of the present invention, the grain size of the positive electrode active material can be 15 nm or more and 20 nm or less. For example, the grain size of the positive electrode active material can be obtained by XRD (X-ray diffraction) analysis and calculated using the Scherrer equation.
[0092] 2. Preparation method of positive electrode active material
[0093] In this specification, a precursor is defined as a chemical substance that participates in a chemical reaction to generate other compounds.
[0094] According to another aspect of the present invention, a method for preparing a positive electrode active material is provided, the method comprising: (S1) preparing a mixture comprising a lithium-permeable layered oxide precursor and a lithium precursor; and (S2) heat-treating the mixture to prepare the positive electrode active material, wherein, in the preparation reaction of the positive electrode active material, the molar content of the lithium precursor is lower than the stoichiometric molar content. Specifically, by controlling the molar content of the lithium precursor to be lower than the stoichiometric molar content in the preparation reaction of the positive electrode active material, primary and secondary particles can grow uniformly, resulting in a positive electrode active material with excellent particle morphology uniformity, and improving the migration speed of lithium ions and the charge / discharge rate of the electrochemical element.
[0095] According to the present invention, the lithium-permeable layered oxide precursor is a precursor of a lithium-permeable layered oxide. In some non-limiting examples, the lithium-permeable layered oxide precursor may include one-quarter nickel and three-quarters manganese carbonate (Ni 0.25 Mn 0.75 CO3).
[0096] In some non-limiting examples, the lithium precursor may be a lithium salt in which lithium is bonded to an anion, specifically lithium carbonate. Alternatively, the lithium precursor may also be referred to as a lithium source.
[0097] In some embodiments of the present invention, the molar content of the lithium precursor may be 0.5 mol% to 3 mol% lower than the stoichiometric molar content. In some embodiments of the present invention, by controlling the molar content of the lithium precursor within the above range, making it lower than the stoichiometric molar content, uniform growth of primary and secondary particles can be achieved, forming a positive electrode active material with excellent particle morphology uniformity, thereby improving the irreversibility of the charge-discharge process caused by the instability of oxidative oxygen.
[0098] In some embodiments of the present invention, step (S2) may include a heat treatment step of subjecting the mixture to a temperature of 800°C to 1100°C for 0.5 hours to 15 hours in an atmospheric environment. Specifically, the heat treatment temperature of the mixture may be 800°C or higher, 850°C or higher, or 900°C or higher; and may be 950°C or lower, 1000°C or lower, 1050°C or lower, or 1100°C or lower; the heat treatment time may be 0.5 hours or higher, 0.7 hours or higher, 0.9 hours or higher, or 1 hour or higher; and may be 1.2 hours or lower, 1.4 hours or lower, 1.6 hours or lower, 1.8 hours or lower, 2.0 hours or lower, 5.0 hours or lower, 10.0 hours or lower, or 15.0 hours or lower. In some embodiments of the present invention, by controlling the heat treatment temperature and heat treatment time of the mixture within the above-mentioned numerical ranges, primary and secondary particles can grow uniformly, achieving a positive electrode active material with excellent particle morphology uniformity, thereby improving the irreversibility of the charge-discharge process caused by the instability of oxidative oxygen.
[0099] 3. Positive electrode
[0100] According to another aspect of the present invention, a positive electrode comprising a positive active material in certain embodiments is provided.
[0101] The positive electrode according to the present invention may include a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector. The positive electrode active material layer may include a positive electrode active material, a conductive agent, and a positive electrode binder.
[0102] For example, the material of the positive electrode current collector is not particularly limited, as long as it does not trigger chemical changes in the battery and has high conductivity. Specifically, materials that can be used as positive electrode current collectors include copper, stainless steel, aluminum, nickel, titanium, sintered carbon, or copper or stainless steel with surface treatments to carbon, nickel, titanium, silver, etc., or aluminum-cadmium alloys, etc. The positive electrode current collector can typically have a thickness of 6 to 20 μm.
[0103] The conductive agent can improve the conductivity between active material particles or between the active material particles and the metal current collector in the electrode, and can prevent the binder from acting as an insulator. The conductive agent may be, for example, a mixture of one or more conductive materials selected from the group consisting of graphite, carbon black, carbon fiber, metal fiber, metal powder, conductive whiskers, conductive metal oxides, activated carbon, and polyphenylene derivatives; more specifically, it may be a mixture of one or more conductive materials selected from the group consisting of natural graphite, artificial graphite, Super-p, acetylene black, Ketjen black, Channel black, furnace black, lamp black, pyrolysis black, Denka black, aluminum powder, nickel powder, zinc oxide, potassium titanate, and titanium oxide.
[0104] For example, the positive electrode binder may be at least one selected from, but not limited to, the following materials: polyvinylidene fluoride co-hexafluoropropylene, polyvinylidene fluoride co-trichloroethylene, polymethyl methacrylate, polyethylhexyl acrylate, polybutyl acrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, ethylene-co-vinyl acetate copolymer, polyethylene oxide, polyacrylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, and cyanoethyl pullulan. Pullulan, cyanoethyl poly(vinyl alcohol) , cyanoethyl cellulose , cyanoethyl sucrose , pullulan , carboxyl methyl cellulose , etc.
[0105] 4. Electrochemical elements
[0106] In this specification, "electrochemical element" is defined as any element that performs an electrochemical reaction. For example, the electrochemical element may be a secondary battery or a supercapacitor, specifically a lithium metal battery or a lithium-ion secondary battery.
[0107] negative electrode
[0108] According to the present invention, the negative electrode may include a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, or lithium metal (Li metal).
[0109] For example, the negative electrode active material layer may include the negative electrode active material, a conductive agent, and a negative electrode binder.
[0110] The negative electrode current collector acts as a channel for electrochemical reactions in the negative electrode active material, transferring electrons from the outside to the negative electrode active material, or receiving electrons from the negative electrode active material and transferring them to the outside. For example, materials that can be used as the negative electrode current collector include copper, stainless steel, aluminum, nickel, titanium, sintered carbon, or materials with surface treatments of carbon, nickel, titanium, silver, etc., on aluminum or stainless steel. More specifically, transition metals such as copper and nickel, which have good adsorption properties for carbon, can also be used as current collectors. For example, the thickness of the negative electrode current collector can be from 6 μm to 20 μm, but its thickness is not limited to this range.
[0111] The conductive agent contained in the negative electrode may be the same as or different from the conductive agent contained in the positive electrode.
[0112] If necessary, the negative electrode active material layer may further include additives. The additives may be, for example, at least one selected from the group consisting of dispersants, plasticizers, antioxidants, lubricants, stabilizers, and antistatic agents.
[0113] diaphragm
[0114] The diaphragm according to the present invention comprises a porous substrate for electrically insulating the positive and negative electrodes to prevent short circuits.
[0115] The constituent materials of the porous substrate are not particularly limited; as long as they possess electrical insulation properties, they can be organic or inorganic materials. The porous substrate may include at least one material selected from the following: polyolefins, polyethylene terephthalate, polybutylene terephthalate, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene ether, polyphenylene sulfide, and polynaphthalene vinylidene; more specifically, it may include polyolefins. Polyolefins not only have excellent coatability but can also reduce the thickness of the separator, thereby increasing the proportion of electrode active material layers in the battery and increasing the capacity per unit volume. Specifically, the weight average molecular weight (Mw) of the polyolefin can be from 100,000 to 500,000 g / mol. If the weight average molecular weight of the polyolefin is below the above range, it may be difficult to obtain sufficient mechanical properties; if it exceeds this range, it may be impossible to achieve the fusing function or it may be difficult to mold. The fusible link function refers to the process where, when the temperature of a secondary battery rises, the thermoplastic resin melts and seals the pores of the porous substrate, thereby blocking the movement of ions and preventing thermal runaway of the battery.
[0116] The thickness of the porous substrate can be 3 to 12 μm, or 5 to 12 μm. If the thickness of the porous substrate is less than this range, it may not be able to fully function as a conductive barrier; if it exceeds this range, it may lead to an excessive increase in the membrane resistance.
[0117] The average diameter of the pores contained in the porous substrate can be from 10 to 100 nm. The pores in the porous substrate are interconnected, allowing gas or liquid to flow from one side of the substrate to the other.
[0118] According to certain embodiments of the present invention, a coating may be applied to at least one side of the porous substrate. Specifically, the coating can improve the mechanical strength and heat resistance of the separator and enhance the ionic conductivity in the secondary battery.
[0119] The coating according to the present invention may contain binder polymers and inorganic particles.
[0120] The adhesive polymer according to the present invention can connect and stably fix inorganic particles. The adhesive polymer may, for example, be selected from one or more mixtures of the following: polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polymethyl methacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, ethylene-co-vinyl acetate copolymer, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, and cellulose acetate propionate. Propionate, cyanoethyl pullullan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullullan, carboxyl methyl cellulose, acrylonitrile-styrene-butadiene copolymer, polyimide, and styrene-butadiene rubber.
[0121] According to another embodiment of the present invention, the weight ratio of inorganic particles to binder polymer (inorganic particles: binder polymer) can be from 50:50 to 99:1, specifically from 70:30 to 95:5. When the content of inorganic particles is lower than the above range, the content of binder polymer increases, which reduces the thermal safety performance of the separator; due to the reduction of gaps formed between inorganic particles, the pore size and porosity decrease, which may lead to a decrease in the final battery performance; while when it exceeds the above range, the content of binder polymer is too low, which may lead to poor internal filling of the coating.
[0122] The inorganic particles according to the present invention can help improve the mechanical strength and heat resistance of a separator for secondary batteries. Specifically, there is no particular limitation as long as the inorganic particles are electrochemically stable. That is, the inorganic particles usable in the present invention refer to those that are within the operating voltage range of the secondary battery to which they are applied (e.g., based on Li / Li + as a reference, 0 to 5 V) do not undergo oxidation and / or reduction reaction.
[0123] For example, when taking inorganic particles as an example, if inorganic particles with a high dielectric constant are used, they can help increase the dissociation degree of an electrolyte salt (e.g., lithium salt) in a liquid electrolyte, thereby improving the ionic conductivity of the electrolyte. For the above reasons, the inorganic particles may be inorganic particles with a dielectric constant of 5 or more, inorganic particles having lithium ion conduction capability, or a mixture of the two.
[0124] The inorganic particles with a dielectric constant of 5 or more may be selected from one or more of the following: Al₂O₃, SiO₂, ZrO₂, AlO(OH), Al(OH)₃, Mg(OH)₂, BaSO₄, TiO₂, BaTiO₃, Pb(Zr x Ti 1-x )O₃ (PZT, wherein 0<x<1), Pb 1- x La x Zr 1-γ Ti γ O₃ (PLZT, wherein 0<x<1, 0<y<1), (1-x)Pb(Mg₁ / ₃Nb₂ / ₃)O₃-xPbTiO₃ (PMN-PT, wherein 0<x<1), HfO₂, SrTiO₃, SnO₂, CeO₂, MgO, NiO, CaO, ZnO and SiC.
[0125] The inorganic particles having lithium ion conduction capability may be selected from one or more of the following: lithium phosphate (Li₃PO₄), lithium titanium phosphate (Li x Ti γ (PO₄)₃, 0<x<2, 0<y<3), lithium aluminum titanium phosphate (LiAlTiP) x O γ based glass (0<x<4, 0<y<13), lithium lanthanum titanate (Li x La γ TiO₃, 0<x<2, 0<y<3), lithium germanium thiophosphate lithium nitride (Li x N γ , 0<x<4, 0<y<2), silicon disulfide based glass and P₂S₅ based glass
[0126] For example, to form a coating of uniform thickness and obtain appropriate porosity, the average particle size (D50) of the inorganic particles can be from 1 nm to 10 μm, specifically from 10 nm to 2 μm, and more specifically from 50 nm to 1 μm. The "average particle size (D50)" refers to the particle size value at which the cumulative frequency of the particle size distribution reaches 50%. This average particle size can be measured using a laser diffraction method. Specifically, the powder to be tested can be dispersed in a dispersion medium and then introduced into a commercially available laser diffraction particle size analyzer (e.g., Microtrac S3500). As the particles pass through the laser beam, the particle size distribution is calculated based on the differences in the diffraction patterns produced by their particle sizes.
[0127] electrolytes
[0128] The electrolyte according to the present invention may include a solvent and a lithium salt.
[0129] The solvent according to the present invention may, for example, be a mixture selected from one or more of the following: propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone, ethyl methyl carbonate (EMC), gamma-butyrolactone (GBL), fluoroethylene carbonate (FEC), methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, propyl acetate, amyl acetate, methyl propionate, ethyl propionate, butyl propionate, etc.
[0130] The lithium salts according to the present invention may include, for example, NO3. - F - Cl - ,Br - I - PF6 - Anions.
[0131] The secondary battery according to the present invention can be cylindrical, prismatic or pouch battery, but is not particularly limited as long as it is a charging and discharging device.
[0132] According to another aspect of the present invention, a battery module comprising the electrochemical element as a unit cell can be provided, as well as a battery pack comprising the module. The battery pack can serve as a power source for one or more large devices, such as: power tools; electric vehicles including electric vehicles (EVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs); or devices for energy storage systems.
[0133] The embodiments of the present invention will be described in detail below to enable those skilled in the art to readily implement the invention. However, this is merely an example and is not intended to limit the scope of the invention. In this specification, terms such as "about" or "substantially" refer to a reasonable range of deviations allowed without significantly altering the final result. These terms can be interpreted as allowing deviations of at least ±5% or at least ±10% without changing the intended meaning of the terms.
[0134] [Manufacturing Preparation Example: Preparation of Coprecipitation Precursors]
[0135] Ni provided by the Korea Atomic Energy Research Institute (KAERI) was prepared. 0.25 Mn 0.75 CO3 coprecipitates the precursor.
[0136] [Experimental Example 1: SEM-EDS Analysis Results of Coprecipitated Precursors]
[0137] Figure 1a Ni prepared according to the manufacturing preparation example 0.25 Mn 0.75 SEM-EDS (Scanning Electron Microscopy-Energy Dispersive Spectroscopy) analysis results of CO3.
[0138] from Figure 1a It can be inferred that the particle size of the coprecipitated precursor is about 7-8 μm, and Ni and Mn are uniformly distributed in a molar ratio of 1:3.
[0139] Figure 1b Ni in the manufacturing preparation example 0.25 Mn 0.75 XRD (X-ray diffraction) analysis results of CO3. Specifically, a Malvern PANalytical Empyrean-type Mo Kα analyzer was used. The wavelength is measured in 0.016° steps within the angular range of 2θ = 5 to 35°.
[0140] from Figure 1b It can be confirmed that the R-3c space group is highly consistent with the results in the existing references, and no other impurities were observed.
[0141] [Preparation Example 1: Preparation of Positive Electrode Active Material]
[0142] Mixing precursors to prepare the mixture stage:
[0143] Weigh Ni according to the composition ratio shown in Table 1 below. 0.25 Mn 0.75 CO3 precursor and Li2CO3 were mixed and ground together using an agate mortar for 30 minutes to prepare a mixture.
[0144] Heat treatment stage of the mixture:
[0145] The above mixture was placed in an alumina boat and tapped, and then heated in an electric furnace at 900°C for 1 hour in an air atmosphere to prepare the positive electrode active material.
[0146] Table 1
[0147]
[0148] [Experimental Example 2: XRD Analysis of Positive Electrode Active Materials]
[0149] Figure 2 The XRD analysis results are for the positive electrode active materials prepared in Comparative Examples 1, 2, and the Examples. Specifically, the XRD analysis results are for the positive electrode active materials prepared in the Malvern PANalytical Empyrean model. The wavelength is measured in 0.016° steps within the angular range of 2θ = 5 to 35°.
[0150] from Figure 2 It can be confirmed that all the positive electrode active materials prepared in Comparative Examples 1, 2 and Examples exhibit a lithium-rich layered structure composed of space groups R-3m and C2 / m.
[0151] [Experimental Example 3: XRD Analysis of Positive Electrode Active Materials]
[0152] Figure 3a The XRD analysis results are for the positive electrode active material of Comparative Example 1. Figure 3b The XRD analysis results are for the positive electrode active material of Comparative Example 2. Figure 3c The XRD analysis results are shown for the positive electrode active material in this example.
[0153] Specifically, the Malvern PANalytical Empyrean model Mo Kα is used. The wavelength was measured in 0.016° steps within the angular range of 2θ = 5 to 35°. Based on the above experimental example 3, the full width at half maximum (FWHM) of the (003) and (104) peaks of each positive electrode active material was calculated, as well as the ratio of the (003) peak intensity I(003) to the (104) peak intensity I(104) I(003) / I(104).
[0154] from Figures 3a to 3c It can be seen that with the adjustment of lithium source content, the XRD peak positions and their full width at half maximum (FWHM) hardly change significantly. Conversely, with the decrease of lithium source content, I... (003) / I (104) The ratio shows an upward trend. Therefore, it can be inferred that by using a lower amount of lithium source (lithium precursor) than the stoichiometric molar ratio, the effect of Li... + / Ni 2+ The cation mixing caused by site exchange effectively prevents the lithium-ion migration channels from being blocked.
[0155] Specifically, in the embodiments, the positive electrode active material (I) (003) / I (104) The ratio is 1.35 or higher.
[0156] [Experimental Example 4: SEM Images and Morphology Analysis of Positive Electrode Active Materials]
[0157] Figure 4a The image shown is a SEM (scanning electron microscope) image of the positive electrode active material in Comparative Example 1. Figure 4b for Figure 4a A magnified image.
[0158] from Figure 4a and 4b As can be seen, compared with Comparative Example 2 described below, the primary and secondary particles grow relatively uniformly, but some particles still exhibit uneven growth.
[0159] Figure 5a This is a SEM image of the positive electrode active material in Comparative Example 2. Figure 5b for Figure 5a A magnified image.
[0160] from Figure 5a and 5b It can be observed that, compared to Ni 25 Mn 75CO3 contains excessively grown primary particles and disordered growth of secondary particles, resulting in decreased particle uniformity.
[0161] Figure 6a The image shown is an SEM image of the positive electrode active material in the example. Figure 6b for Figure 6a A magnified image.
[0162] from Figure 6a and 6b It can be seen that in the positive electrode active material prepared according to the embodiments of the present invention, the primary and secondary particles grow uniformly, and the uniformity of particle morphology is significantly improved.
[0163] [Experimental Example 5: TEM cross-sectional image of the positive electrode active material]
[0164] Figure 7a The images shown are cross-sectional TEM (transmission electron microscope) images of the positive electrode active materials of Comparative Examples 1, 2 and Examples.
[0165] from Figure 7a It can be seen that in Comparative Example 2, the disordered growth of the primary particles resulted in larger internal pores. Compared with Comparative Example 2, in Comparative Example 1 and the embodiments, as the lithium source content decreased, the primary particles aligned towards the particle center, leading to a reduction in the size of the internal pores.
[0166] Figure 7b TEM images of the atomic arrangement analysis of the positive electrode active materials of Comparative Examples 1, 2 and Examples.
[0167] from Figure 7b As can be seen, in Comparative Example 2, a rock-salt structure layer was formed on the surface of the positive electrode active material, while in the examples, a uniform and thin spinel structure was observed. The rock-salt structure is an electrochemically inert phase, thus providing significant resistance to lithium-ion migration or charge transport. This property reduces the migration rate of lithium ions within the rock-salt structure, and due to its identical crystal orientation with the internal layered structure, it cannot effectively suppress non-uniform particle growth.
[0168] Conversely, the positive electrode active material in the examples, due to the formation of a spinel structure on its surface, suppresses the irregular growth of primary particles and causes them to align directionally within the secondary particles, thereby suggesting an improved lithium-ion migration rate. It can be inferred that the charge-discharge rate of the electrochemical device is also expected to be improved.
[0169] [Experimental Example 6: Analysis of Particle Surface Electronic Structure by Electron Energy Loss Spectroscopy]
[0170] Figure 8 The results are based on the electron energy loss spectroscopy (EELS) analysis of the positive electrode active materials in Comparative Example 2 and the examples.
[0171] from Figure 8 It can be seen that in Comparative Example 2, some Mn was detected at the Mn L-edge. 2+ It was confirmed that it originated from M formed on the surface. 2 + O 2- Rock-salt structural layer. In the positive electrode active material of the embodiment, Mn was detected only near the surface. 3+ It was confirmed that it originated from LiMn 3.5+ The manganese element contained in the structure of spinel 2O4.
[0172] [Experiment Example 7: Analysis of the Pore Structure of Positive Electrode Active Materials by Small-Angle X-ray Scattering]
[0173] Figure 9a The results of SAXS (small-angle X-ray scattering) analysis of the positive electrode active materials of Comparative Examples 1, 2, and the Examples are shown. The SAXS plot represents the intensity of X-rays as the scattering vector (Q) changes.
[0174] Figure 9b The volume fraction analysis results (SAXS analysis) of micropores and macropores of different radii in the positive electrode active materials of Comparative Examples 1, 2 and Examples are shown.
[0175] Specifically, the prepared lithium-impregnated layered cathode material was uniformly dispersed on a tape for sampling. A Rigaku NANOPIX Lab-SAXS instrument was used, employing Cu Ka (wavelength: The tests were conducted with distances (SDDs) between the sample and the detector being 1.3m and 0.15m, respectively.
[0176] Test conditions are set to Q range Where Q = [4π / λ]*sin(θ / 2), Q is the magnitude of the scattering vector, and θ is the scattering angle. Data calibration was performed using the standard substance AgBe (silver stearate), and data processing was performed in Igor software using the HANAROSANS data analysis program (provided by KAERI).
[0177] Table 2 below shows the volume data of different types of pores compiled based on the results of SAXS (small angle X-ray scattering) analysis.
[0178] Table 2
[0179]
[0180] According to Table 2 above, Figure 9a and Figure 9b It can be seen that as the lithium source content increases, the radius and volume of the macropores increase. At the same time, the lower the lithium source content, the smaller the total pore volume.
[0181] In this invention, unlike the conventional method of adding excessive lithium source, by reducing the content of added lithium source, the macropores and micropores in the positive electrode active material can be precisely controlled, thereby achieving uniform growth of positive electrode active material particles and exhibiting excellent electrochemical performance.
[0182]
Preparation Example 2: Preparation of a Button Cell
[0183] Preparation of the positive electrode:
[0184] The positive electrode active material, conductive agent (Super P), and binder (polyvinylidene fluoride) from Preparation Example 1 were mixed at a mass ratio of 80:10:10, and then a solvent (N-methylpyrrolidone) was added. The mixture was then stirred at 20 rpm for 1 hour using a Pulverisette 23 Mini Mill to prepare a positive electrode slurry with a solid content of 50 wt%. The above positive electrode slurry was then stirred at approximately 3 mg / cm³... 2 The coating amount was applied to an aluminum current collector with a thickness of about 15 μm on one side, and then dried in a vacuum oven at 100°C for 12 hours to prepare the positive electrode.
[0185] Preparation of the counter electrode (negative electrode):
[0186] Prepare a lithium metal electrode with a thickness of about 1 mm as the counter electrode.
[0187] Preparation of the diaphragm:
[0188] A single-layer polypropylene diaphragm was prepared. 2400, thickness approximately 25μm).
[0189] Electrolyte injection steps:
[0190] In an argon-atmospheric glove box, the electrode assembly consisting of the positive electrode, separator, and counter electrode was injected into the electrolyte and assembled into a CR-2032 coin cell. The electrolyte used was a mixed solvent of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a volume ratio of 2:4:4, in which 1.2 M of LiPF6 was dissolved.
[0191] [Experiment Example 8: Evaluation of the Charge and Discharge Performance of Button Cells]
[0192] Figure 10aThis is a charge / discharge curve of the button cell corresponding to Comparative Example 1. Figure 10b This is the charge and discharge curve of the button cell corresponding to Comparative Example 2. Figure 10c This is a charge / discharge curve of the coin cell corresponding to the embodiment. Specifically, under 30°C conditions, the current density was set to (1C = 250 mA / g), and the voltage range was set to 2.0–4.7V (vs. Li / Li). + The battery charge and discharge performance was evaluated using a battery charge and discharge tester.
[0193] Table 3
[0194]
[0195] from Figures 10a to 10c As shown in Table 3, compared with Comparative Examples 1 and 2, the ratio of micropore volume to macropore volume in the examples is less than 27, thereby achieving higher initial charging capacity, initial discharging capacity and initial coulombic efficiency.
[0196] [Experiment Example 9: Cycle Life Performance Evaluation of Button Cells]
[0197] Figure 11 This is a graph showing the capacity change of the coin cells corresponding to Comparative Examples 1, 2, and the Examples at different cycle counts. After initial formation at 2.0-4.7V (vs. Li / Li+), the upper limit voltage was set to 4.5V (vs. Li / Li+), and the remaining test methods were the same as in Experimental Example 8, in order to evaluate the life performance of the coin cells.
[0198] from Figure 11 It can be seen that Comparative Example 2 (Li 5 mol%) did not achieve its initial capacity, but its capacity gradually increased during continuous cycling, although its reversible capacity was very low. The electrochemical element of Comparative Example 1 (Li 0 mol%) experienced a relatively rapid capacity decrease, but still retained 80% of its initial capacity after 200 charge-discharge cycles.
[0199] In contrast, the example (Li-2mol%) exhibited the highest capacity and retention (90%), demonstrating that the particle morphology of the prepared lithium-bound layered cathode active material has a significant impact on electrochemical performance.
[0200] [Experimental Example 10: Analysis of Oxidation State Changes in Transition Metals]
[0201] Figure 12 These are X-ray absorption spectroscopy (XAS) results showing the transition metal oxidation state changes of the positive electrode active material in the coin cells of Comparative Examples 1, 2, and the Examples. Specifically, Figure 12 (a) shows the measurement results of the Ni K side. Figure 12 (b) shows the measurement results of the Mn K edge.
[0202] After charging and discharging, the coin cells were disassembled in an argon-atmospheric glove box. The separated electrodes were then immersed in a dimethyl carbonate solution to remove impurities formed on the electrode surface. To prevent contact with external air, the electrodes were sealed with a polyimide film, and the Ni K-edge and Mn K-edge regions were measured using the 7D-XAFS beamline at the Pohang Accelerator Laboratory.
[0203] from Figure 12 It can be seen that Ni was further oxidized in Comparative Example 2 (Li 5mol%), while Mn showed the same 4+ oxidation state in all comparative examples and sample samples.
[0204] Figure 13a The results are X-ray absorption spectra of the changes in the oxidation states of Ni and Mn transition metals during the charging and discharging process of the coin cell of Comparative Example 1.
[0205] from Figure 13a Comparing the pristine and fully discharged states reveals that the oxidation state of Ni can recover to its initial state after charging and discharging, while Mn undergoes partial reduction in the fully discharged state. This is attributed to the fact that Mn contributes a significant amount of capacity during discharge, leading to partial material degradation.
[0206] Figure 13b The results are X-ray absorption spectra of the changes in the oxidation states of Ni and Mn during the charging and discharging process of the electrochemical element in Comparative Example 2.
[0207] from Figure 13b It can be seen that in Ni 2+ / Ni 4+ Within the reaction range (Pristine to Half-charged), Ni underwent oxidation while Mn showed no significant change. Subsequently, within the flat potential range associated with the oxygen reaction, changes in the shape of the K-edge spectral lines due to variations in the adjacent local environment were observed. Furthermore, neither Ni nor Mn recovered to their initial states under fully discharged conditions.
[0208] Figure 13c The X-ray absorption spectrum results are the changes in the oxidation states of Ni and Mn of the electrochemical element during the charging and discharging process in the embodiment.
[0209] from Figure 13c As can be seen, the embodiments and comparative examples show the same trend. However, under fully discharged conditions, the X-ray absorption spectrum of Mn in the embodiments is closer to the pristine state than that in the comparative example. This confirms that the degree of reduction of the oxidation state of Mn in the embodiments is lower than that in the comparative example. This indicates that the structure of the embodiments has better resistance to degradation than that of the comparative example.
[0210] The features described in any of the above embodiments may be combined with other embodiments unless explicitly stated otherwise. Furthermore, although preferred embodiments of the invention have been described in detail above, the scope of the invention is not limited thereto. All modifications and improvements made using the basic concept of the invention as defined in the following claims are also within the scope of the invention.
Claims
1. A positive electrode active material, characterized in that, Comprises lithium-excess layered oxide, and the R value calculated according to the following formula 1 does not exceed 27: 【Equation 1】R=(P A / P B ), Among them, based on the analysis of small-angle X-ray scattering, P A The volume of macropores included in the positive electrode active material is expressed in cm³. 3 / g, P B The volume of the micropores included in the positive electrode active material is expressed in cm³. 3 / g, wherein the macropore refers to the pore radius is Volume fraction within the range, in units of The sum of, wherein the micropore refers to the pore diameter radius is The sum of volume fractions within the range.
2. The positive electrode active material according to claim 1, characterized in that, Comprises a compound represented by the following general formula 1: [General Formula 1] xLi2MnO3·(1-x)Li[Mn a M1 b M2 c O2, wherein 0<x<1, and a+b+c=1, 0<a<1, 0≤b<1, 0≤c<1, M1 and M2 are different transition metals, and are Ni or Co.
3. The positive electrode active material according to claim 1, characterized in that, Comprises a compound represented by the following general formula 2: [General Formula 2] y[LiMn p Ni (1-p-q-r) Co q M3 r O2]·(1-y)[Li2Mn s M4 (1-s) O3], wherein M3 and M4 are each independently selected from one of Zr, Al, Re, V, Cr, Fe, Ga, Si, B, Ru, Ti, Nb, Mo, Mg, W, Na and Pt; and 0.500<y<0.800, 0.450<p<0.650, 0≤q≤0.025, 0≤r≤0.100, 0.900≤s≤1.
000.
4. The positive electrode active material according to claim 1, characterized in that, The following X-ray diffraction analysis results are met: (003) X-ray intensity I of the crystal plane diffraction peak (003) X-ray intensity I of the diffraction peak of the (104) crystal plane (104) The ratio I (003) / I (104) Not less than 1.
31.
5. The positive electrode active material according to claim 1, characterized in that, Based on small-angle X-ray scattering analysis, the volume of the macropore is 0.35 cm³. 3 / g or more and not exceeding 0.45cm 3 / g.
6. The positive electrode active material according to claim 1, characterized in that, According to small-angle X-ray scattering analysis, the volume of the micropore is 0.017 cm³. 3 / g or more and not exceeding 0.025cm 3 / g.
7. The positive electrode active material according to claim 1, characterized in that, According to small-angle X-ray scattering analysis, the total pore volume contained in the positive electrode active material does not exceed 0.475 cm³. 3 / g.
8. A method for preparing a positive electrode active material, characterized in that, Comprises: (S1) a step of preparing a mixture comprising a lithium-excess layered oxide precursor and a lithium precursor; and (S2) a step of heat-treating the mixture to prepare a positive electrode active material, wherein in the synthesis reaction of the positive electrode active material, the molar content of the lithium precursor is lower than the stoichiometric molar content.
9. The method for preparing the positive electrode active material according to claim 8, characterized in that, The molar content of the lithium precursor is 0.5 mol% to 3 mol% lower than the stoichiometric molar content.
10. The method for preparing the positive electrode active material according to claim 8, characterized in that, The step (S2) comprises: heat-treating the mixture in an atmospheric atmosphere at a temperature between 800°C and 1100°C for 0.5 hours to 15 hours.
11. A positive electrode active material, characterized in that, A positive electrode active material obtained by the method for preparing a positive electrode active material according to claim 8.
12. A positive electrode, characterized in that, Comprises the positive electrode active material according to any one of claims 1 to 8.
13. An electrochemical device, characterized in that, Comprises: The positive electrode according to claim 12; a negative electrode; a separator disposed between the positive electrode and the negative electrode; and an electrolyte.